Gambaran Komunikasi Interpersonal Petugas Pendaftaran Pasien Terhadap Kepuasan Pelayanan di Puskesmas Kota Matsum - Angelia Putriana; Andi Mei Putra Mendrofa (MUKASI: Jurnal Ilmu Komunikasi, 2023)
Interpersonal communication or interpersonal communication is communication that refers to the process of closeness, the intimacy of the communication, with the aim of the message conveyed having a direct effect, therefore interpersonal communication begins with a psychological approach, building closeness and intimacy. Satisfaction or dissatisfaction is a conclusion from the interaction between expectations and experience after using the services or services provided. This research took place from May to September at the Matsum City Health Center. This research method is descriptive qualitative with purposive sampling data collection technique is a scientific observation and is carried out carefully and carefully so that the results become more accurate and precise which aims to see the description of interpersonal communication of patient registration officers on service satisfaction at the Matsum City Health Center. The subjects of this study were registration officers and patients who interacted with each other during the registration process. The collection methods used were interviews and observation. Based on this study, the description of interpersonal communication carried out by the registration officer to the patient is in accordance with the SOP (Standard Operating Procedure), Interpersonal communication between the registration officer and the patient is intertwined with several questions from the registration officer who make the patient feel cared for so that from this communication a sense of satisfaction arises in the patient. This study suggests to further improve the communication of registration officers interpersonal communication that is more effective, so as to maintain the satisfaction of patients seeking treatment at the Matsum City Health Center.